Diversity, Distribution and Occurrence of Fishes in Begnas Lake, Pokhara, Nepal (ZOO-Journal, 2019)
Present paper deals with the diversity of fishes in Begnas Lake, Pokhara. Fishes were identified and their occurrence, average size range, weight and market price were determined. Altogether 17 species of fishes belonging to five orders, seven families and 17 genera were recorded, of which 11 species were indigenous, while six species were exotic. Family cyprinidae was dominant in terms of both species composition and occurrence. Knowledge of fish diversity has been expected as a useful tool for both quality and quantity harvesting of fish as well as for future studies.